Tex - Hinton, S. E. (New York : Bantam Doubleday Dell Books for Young Readers, 1989)
The love between two teen-age brothers helps to alleviate the harshness of their usually parentless life as they struggle to grow up.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
6.0
Young Adult
Keywords: Brothers -- Fiction; Self-realization -- Fiction; Self-reliance -- Fiction; Brothers -- Fiction; Self-realization -- Fiction; Self-reliance -- Fiction